Superior Silencing by 2′,4′-BNANC-Based Short Antisense Oligonucleotides Compared to 2′,4′-BNA/LNA-Based Apolipoprotein B Antisense Inhibitors - Yamamoto, Tsuyoshi; Yasuhara, Hidenori; Wada, Fumito; Harada-Shiba, Mariko; Imanishi, Takeshi; Obika, Satoshi (Journal of Nucleic Acids, 2012)
The duplex stability with target mRNA and the gene silencing potential of a novel bridged nucleic acid analogue are described. The analogue, 2′,4′-BNANC antisense oligonucleotides (AONs) ranging from 10- to 20-nt-long, targeted apolipoprotein B. 2′,4′-BNANC was directly compared to its conventional bridged (or locked) nucleic acid (2′,4′-BNA/LNA)-based counterparts. Melting temperatures of duplexes formed between 2′,4′-BNANC-based antisense oligonucleotides and the target mRNA surpassed those of 2′,4′-BNA/LNA-based counterparts at all lengths. An in vitro transfection study revealed that when compared to the identical length 2′,4′-BNA/LNA-based counterpart, the corresponding 2′,4′-BNANC-based antisense oligonucleotide showed significantly stronger inhibitory activity. This inhibitory activity was more pronounced in shorter (13-, 14-, and 16-mer) oligonucleotides. On the other hand, the 2′,4′-BNANC-based 20-mer AON exhibited the highest affinity but the worst IC50 value, indicating that very high affinity may undermine antisense potency. These results suggest that the potency of AONs requires a balance between reward term and penalty term. Balance of these two parameters would depend on affinity, length, and the specific chemistry of the AON, and fine-tuning of this balance could lead to improved potency. We demonstrate that 2′,4′-BNANC may be a better alternative to conventional 2′,4′-BNA/LNA, even for “short” antisense oligonucleotides, which are attractive in terms of drug-likeness and cost-effective bulk production.